Prussian blue nanosphere-embedded in situ hydrogel for photothermal therapy by peritumoral administration - Jijun Fu; Bo Wu; Minyan Wei; Yugang Huang; Yi Zhou; Qiang Zhang; Lingran Du (Elsevier, 2019)
To establish an injectable hydrogel containing Prussian blue (PB) nanospheres for photothermal therapy against cancer, PB nanospheres were prepared by one-pot synthesis and the thermosensitive Pluronic F127 was used as the hydrogel matrix. The PB nanospheres and the hydrogel were characterized by shape, particle size, serum stability, photothermal performance upon repeated 808 nm laser irradiation, as well as the rheological features. The effect of the PB nanospheres and the hydrogel were evaluated qualitatively and quantitatively in 4T1 mouse breast cancer cells. The retention, photothermal efficacy, therapeutic effects and systemic toxicity of the hydrogel were assessed in a tumor-bearing mouse model. The PB nanospheres had a diameter of about 150 nm and exhibited satisfactory serum stability, photo-heat convert ability and repeated laser exposure stability. The hydrogel encapsulation did not negatively influence the above features of the photothermal agent. The nanosphere-containing hydrogel showed a phase transition at body temperature and, as a result, a long retention time in vivo. The photothermal agent-embedded hydrogel displayed promising photothermal therapeutic effects in the tumor-bearing mouse model with little-to-no systemic toxicity after peritumoral administration. Keywords: Prussian blue, Nanospheres, Hydrogel, Thermosensitive, Injectable, In situ, Photothermal